Implementation of Artificial Intelligence for Green Human Resource Management - Emilia, Sindi Budi (Universitas Bumigora, 2025)
The development of technology, particularly in the field of Artificial Intelligence (AI), has had aprofound impact on various aspects of organizational management, including Human Resource Manage- ment (HRM). This study aims to examine the application of Artificial Intelligence in HR that is oriented towards environmentally friendly principles. This study employs a qualitative approach with a case study method, where data collection techniques are carried out through in-depth interviews with all parties directly involved in human resource management at Company X, namely one company owner and 13 employees. The study’s results indicate that Company X has effectively implemented AI technology in its human resource management. The application of this technology is not intended to replace the role of humans in HR, but to support and improve work efficiency. The AI software used enables companies to monitor employee activities and productivity more efficiently and in greater detail. The entire pro- cess in human resource management, from recruitment to employee management, is still carried out by involving humans. The use of this technology has also been shown to minimize human error and lighten the conventional workload of the HRD department, making work more time-saving and efficient. The theoretical implications of this study’s findings suggest that integrating AI in HR can strengthen modern management theory, which emphasizes the importance of efficiency, effectiveness, and sustainability in organizational management.